An Empirical Study on the Theory of Planned Behavior: the Effect of Gender on Entrepreneurship Intention - Dian Palupi; Bambang Hadi Santoso (Universitas Hayam Wuruk Perbanas, 2017)
This study aimed to examine the effect of gender on entrepreneurship intention through attitude as a mediating variable of entrepreneurship, subjective norms, and perceived behavior controls, and their implications. The sample of this research consisted of 429 students from four state and private universities in East Java. The sample was taken by non-random sampling that is through accidental sampling. In addition, the sample was taken from the students who were still taking the lecture. This was done to facilitate the distribution of questionnaires and the return and accuracy of answers given by students. The analysis technique used in this research is quantitative data analysis technique using Path Analysis modeling. The results shows that, gender directly affects the intention of entrepreneurship. The effect of gender on entrepreneurial intention is mediated by attitude toward entrepreneurship, subjective norms, and perceived behavioral control.